On the phonological interpretation of the falling diphthongs in Danish - Basbøll, Hans (Annual Report of the Institute of Phonetics University of Copenhagen, 1975)
'Diphthong' is here taken to be a phonetic and not a phonological concept. The meaning of the term 'diphthong' is discussed in section 2, and the classification of (Danish) diphthongs into rising and falling in section 3.1. Section 3 contains proposals as to the phonological treatment of the falling diphthongs in Danish from several angles. In section 4, finally, we shall ask and try to answer the question: can 'diphthong' in any sense be considered a phonologically (i.e. functionally) relevant concept in Danish?